2012
DOI: 10.4236/msa.2012.38077
|View full text |Cite
|
Sign up to set email alerts
|

Co-Precipitation Synthesis and Characterization of Nanocrystalline Zinc Oxide Particles Doped with Cu<sup>2+</sup> Ions

Abstract: Nanocrystalline Cu-doped ZnO particles were synthesized by the co-precipitation method. The composition, structural, optical and magnetic characterizations were performed by energy dispersive X-Ray spectroscopy, X-Ray diffraction, UV-Visible spectrometer, and vibrating sample magnetometer. The results confirmed that nanocrystalline Cu-doped ZnO particles have a hexagonal wurtzite structure with a high degree of crystallization and a crystallite size of 10 -16 nm. For Cu above 11 at%, the X-Ray diffraction patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…As the particle size decreases on doping, the surface to volume ratios become larger which can lead to attachment of more OH groups. Similar behaviour of PL spectra was also found by other workers on doping host ZnO [16].…”
Section: Pl Studysupporting
confidence: 89%
See 1 more Smart Citation
“…As the particle size decreases on doping, the surface to volume ratios become larger which can lead to attachment of more OH groups. Similar behaviour of PL spectra was also found by other workers on doping host ZnO [16].…”
Section: Pl Studysupporting
confidence: 89%
“…Aluminium introduces compressive stress and strain whereas Cu develops longitudinal stress and strain on doping and co-doping a sample of ZnO. In case of co-doping, mutual interaction between Cu and Al atoms and their segregation in grain boundaries contribute to longitudinal stress and strain [16,17].…”
Section: Xrd Studymentioning
confidence: 99%
“…The relatively strong rbonding of Fe in the host lattice of ZnO significantly reduces ZnO nanoparticle dissolution. Conversely, Cu doping is known to strain the ZnO crystal structure (Mukhtar et al 2012), hence leading to increased dissolution of ZnO and shedding of more Zn ?2 ions. Thus, the substitution of Cu in ZnO lattice affects the ionization of ZnO during exposure and these effects are not in line with Fe-doped ZnO.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The intensity behind doping is to modify the properties of nanoparticles. Further, to enhance the magnetization and their utilization in DMS and spintronics, doping of transition metal ions such as Ni, Co, Mn, and Ni are carried out by the researchers [10]. A number of studies have reported on Co doped ZnO nanoparticles [11].…”
Section: Introductionmentioning
confidence: 99%